'The penis is a weapon of power': a feminist and hate crime interpretation of male sexual victimisation. Issue 1 (2nd January 2018) - Javaid, Aliraza
ABSTRACT: This paper critically discusses understandings of male rape and male sexual assault in the UK, using a sample size of 70 respondents who consist of police officers and voluntary agency practitioners to shed light on their understandings and explanations of male rape, since they intimately deal with male rape victims/offenders. An analysis of how they make sense of male rape, using radical feminist and hate crime perspectives as frameworks to elucidate male rape and male sexual assault, reveals nuanced findings that suggest that men rape other men as a way in which to exercise power and control, but also as a way in which to unleash homophobia. Thus, this study found that male rape can be carried out as a form of hate crime and homophobic violence, demonstrating the prejudicial hatred the sexual offender has for his male rape victim. This finding is absent from the current literature on male rape. While there are some similarities to women's rapes and sexual assaults, in terms of rape being about power and control, male rape is unique in that it is characterised by hatred not only in a gang male rape context, but also in a one-to-one context. This finding suggests some rather explanatory differences between male rape and female rape. The study begins an important exploration of the different explanations of male rape and male sexual assault. It encourages further theoretical and empirical research of male sexual victimisation.